2007
DOI: 10.1186/cc5670
|View full text |Cite
|
Sign up to set email alerts
|

Liver dysfunction associated with artificial nutrition in critically ill patients

Abstract: Introduction Liver dysfunction associated with artificial nutrition in critically ill patients is a complication that seems to be frequent, but it has not been assessed previously in a large cohort of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Likewise, the results of a multicentre study by Grau et al . showed no impairment of liver function within the first six days of TPN [ 57 ]. In the light of these findings we do not attribute any major role to TPN in the pathogenesis of SSC-CIP in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the results of a multicentre study by Grau et al . showed no impairment of liver function within the first six days of TPN [ 57 ]. In the light of these findings we do not attribute any major role to TPN in the pathogenesis of SSC-CIP in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the SPN trial showed that this individualized energy supply obtained by EE measurement in 65% of patients was rewarding in terms of reduction of nosocomial infections in severely ill ICU patients requiring prolonged ICU treatment [ 38 ]. Grau and colleagues have shown that liver alterations (defined as cytolysis, cholestasis or a combination of both) during enteral or parenteral feeding occur frequently if energy delivery exceeds 27 kcal/kg/day, and add to those liver alterations caused by sepsis and multiple organ failure [ 42 ]; the difference becomes significant after day 11 in patients on PN, ED producing less alteration related to lower energy intakes.…”
Section: Energy Requirementsmentioning
confidence: 99%
“… Multivariate model A multiple linear regression model was constructed to study the relationship between each LFT variation as a continuous variable and the amount of FO given adjusted in accordance with four important variables of liver co-morbidity: Presence of sepsis when each liver parameter presented the highest value. According to the American College of Chest Physician/Society of Critical Care Medicine (ACCP/SCCM) consensus conference, sepsis was established when the patient presented at least two of the following criteria: (a) body temperature ≥38 °C or ≤36 °C, (b) tachycardia with heart rate ≥90 beats/min, (c) tachypnea with paCO 2 ≤ 32 mmHg or mechanical ventilation; (d) leukocytes >12x10 9 cells/L [ 14 ]. LOS in ICU considered as the number of days that the patient stayed in ICU.…”
Section: Methodsmentioning
confidence: 99%